Teacher Efforts Towards the Development of Students’ Mathematical Reasoning Skills - Mukuka, Angel; Balimuttajjo, Sudi; Mutarutinya, Vedaste (My University, 2022)
Research shows that enhanced mathematical reasoning leads to increased conceptual understanding and application of mathematical knowledge to various practical situations. However, the identification of classroom practices that support the development of students’ mathematical reasoning and the assessment of teacher efforts towards the development of such skills have received little attention in existing research. An explanatory sequential mixed methods research design was employed. Sixty-two teachers of mathematics from six randomly selected public secondary schools within one district completed the questionnaire. Teachers’ questionnaire responses were complemented by lesson observations conducted in six randomly selected grade 11 classrooms from all participating schools. Results show that more than 53% of the teachers reported having been employing classroom activities aimed at deepening students’ mathematical reasoning skills. Nevertheless, lesson observations revealed some missed opportunities for enhancing students’ mathematical reasoning skills. The absence of or little emphasis on thought-provoking tasks, modeling with mathematics, students’ exposure to investigating mathematical structures, use of multiple representations, and collaboration among students were observed. These findings demonstrate a need for more professional development opportunities aimed at orienting both in-service and pre-service teachers on effective classroom practices that are bound to deepen students’ mathematical reasoning.
Keywords: Classroom practices; Mathematics classroom; Mathematical reasoning skills